Disciplinary Movements, the Civil Rights Movement, and Charles Keil’s Urban Blues - Sakakeeny, Matt (Current Musicology, 2005)
Charles Keil was in his midtwenties when he published his first book, Urban Blues (1966a), based on his master’s thesis in anthropology at the University of Chicago. In many ways, it was the summation of his experiences and encounters up to that point: a childhood in rural Connecticut where his grandfather raised pigs; a love of jazz that began with drum lessons from his uncle (an example of what colleague Steven Feld described as “white male bonding through black music” [Keil and Feld 1994:2]); undergraduate schooling at Yale that included travel to the West Indies and Nigeria; 1960s countercultural activism intensified by a relationship with Malcolm X; a tumultuous graduate school experience under the tutelage of Clifford Geertz, David Schneider, and Marshall Sahlins in anthropology, Leonard Meyer in musicology, and Alan Merriam in ethnomusicology; and finally fieldwork in the theaters, nightclubs, radio stations, recording studios, and tour buses connected to the bustling blues scene in Chicago. The appearance of Urban Blues was not revolutionary because it came from the hand of a humanist prodigy, but because Keil approached a modern, urban African American musical style with such rigor. In the current disciplinary climate of critical musicology, ethnomusicology, anthropology, and Black Studies, it is difficult to grasp that Urban Blues was not only one of the first scholarly texts based on fieldwork in urban Afro-America, but was also one of the first ethnographic monographs dedicated to an American popular music form, and was the first to eschew transcription and detailed musical-structural analysis in favor of a sociocultural approach.